2016
DOI: 10.1016/j.celrep.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

BRD4 Phosphorylation Regulates HPV E2-Mediated Viral Transcription, Origin Replication, and Cellular MMP-9 Expression

Abstract: SUMMARY Post-translational modification can modulate protein conformation and alter binding partner recruitment within promoter regulatory regions. Here, we find that bromodomain-containing protein 4 (BRD4), a transcription cofactor and chromatin regulator, uses a phosphorylation-induced switch mechanism to recruit E2 protein encoded by cancer-associated human papillomavirus (HPV) to viral early gene and cellular matrix metalloproteinase-9 (MMP-9) promoters. Enhanced MMP-9 expression, induced upon keratinocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
121
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(125 citation statements)
references
References 34 publications
4
121
0
Order By: Relevance
“…3D). Thus, Y102E is unable to interact with the established E2-binding CTM of Brd4 but can bind in vitro to the BID region, which is known to be mediated by the E2 C-terminal DNA-binding domain (DBD) (40).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…3D). Thus, Y102E is unable to interact with the established E2-binding CTM of Brd4 but can bind in vitro to the BID region, which is known to be mediated by the E2 C-terminal DNA-binding domain (DBD) (40).…”
Section: Resultsmentioning
confidence: 99%
“…3C). It was recently reported that distinct domains in Brd4 undergo conformational changes to interact with p53 (39) and HPV E2 (40). We tested the basic residue-enriched interaction domain (BID) for an association with BPV-1 E2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations